American Opinion Toward Jews During the Nazi Era: Results from Quota Sample Polling During the 1930s and 1940s. (6th March 2014) - Welch, Susan
<x xml:space="preserve">Abstract</x> Objective We investigate Americans' opinions about European and American Jews between 1938 and 1945, the period from the height of Nazi domestic power to the end of the war in Europe. Methods Several surveys of U.S. public opinion between 1938 and 1945, reweighted to reflect national population parameters, were examined to uncover both aggregate patterns of responses and predictors of pro‐ and anti‐Jewish sentiment. Results We find that individuals' social status, gender, partisan learning, and, to some extent, region affected their views on Jewish Americans and on European Jews. Conclusion Roosevelt's policies of speaking out against Hitler's atrocities, but yet doing nothing to facilitate more Jews to enter the United States as refugees, reflected the complexities of Americans' opinions about Jews here and abroad but led to failure to provide a safe haven for those thousands of Jewish refugees who might have fled before the war.